Epidemiology of Aspergillus keratitis at a tertiary care eye hospital in South India and antifungal susceptibilities of the causative agents. Issue 1 (10th April 2012) - Manikandan, Palanisamy; Varga, János; Kocsubé, Sándor; Anita, Raghavan; Revathi, Rajaraman; Németh, Tibor Mihály; Narendran, Venkatapathy; Vágvölgyi, Csaba; Panneer Selvam, Kanesan; Shobana, Coimbatore Subramanian; Babu Singh, Yendremban Randhir; Kredics, László
Summary In recent years, Aspergillus species are reported frequently as aetiological agents of fungal keratitis in tropical countries such as India. Our aim was to evaluate the epidemiological features of Aspergillus keratitis cases over a 3‐year period in a tertiary eye care hospital and to determine the antifungal susceptibilities of the causative agents. This study included culture proven Aspergillus keratitis cases diagnosed between September 2005 and August 2008. Data including prevalence, predisposing factors and demography were recorded, the isolates were identified by morphological and molecular methods and the minimum inhibitory concentration values of antifungal agents towards the isolates were determined by the microdilution method. Two hundred Aspergillus isolates were identified among 1737 culture proven cases. Most of the aspergilli (75%) proved to be A. flavus, followed by A. fumigatus (11.5%). Sixteen (8%) isolates belonged to species that are recently identified causative agents of mycotic keratitis. Most of the infected patients (88%) were adults ranging from 21 to 70 years of age. Co‐existing ocular disease was confirmed in 16.5% of the patients. Econazole, clotrimazole and ketoconazole were notably active against A. flavus. Aspergillus keratitis is a significant problem in patients with ocular lesions in South‐Indian States, warranting early diagnosis and initiation of specific antifungal therapy to improve outcome.